Introducing a skin assessment tool in a tertiary Neonatal Intensive Care Unit. Issue 1 (February 2023) - Dineen, Fiona; Raghu, Krishna; Harris, Deborah; Brown, Bernadette
Abstract: Objective: The aim of this project was to find and put in place a functional skin assessment tool that would be specific to neonates of any gestational age. The purpose was to find a skin assessment tool that would; Assess and optimise the preservation of the neonate's skin integrity. Highlight babies that are at possible risk of skin breakdown. Assist nurses to assess neonatal skin on a regular basis, thus to prevent skin damage and help care for neonates with skin damage, in delivering a recommend bundle of care. Design: Showing the development and introduction of a neonatal skin assessment tool. The Neonatal Intensive Care Unit (NICU), where this project took place was in Wellington Hospital, based in Wellington, New Zealand (NZ). This NICU is one of the six tertiary NICU's within NZ, it has a yearly average of 875 admissions.